1994
DOI: 10.1002/anxi.3070010402
|View full text |Cite
|
Sign up to set email alerts
|

Course and outcome in panic disorder: A review of recent follow‐up studies

Abstract: This paper reviews the methodologic considerations that are important in evaluating and interpreting panic disorder outcome studies and the results of the most well-designed of these studies. Sixteen studies that used modern diagnostic criteria and interviewed at least 25 patients on at least two occasions over a minimum follow-up period of one year are reviewed. Results show that, despite the availability of effective anti-panic treatments, panic disorder remains a chronic illness. While most patients improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 40 publications
3
36
1
2
Order By: Relevance
“…Although depression co-occurred with PD less frequently at baseline than is usually reported in studies of PD in psychiatric settings, the prevalence of co-morbid depression after nine years was similar to that reported in a review of follow-up studies of PD (55). Three possible explanations to the panic-depression co-morbidity have been suggested: depression as a causal risk factor for panic, panic as a causal risk factor for depression or panic and depression both as consequences of another disorder (115).…”
Section: Outcome Of Panic Disorder At Follow-upsupporting
confidence: 81%
“…Although depression co-occurred with PD less frequently at baseline than is usually reported in studies of PD in psychiatric settings, the prevalence of co-morbid depression after nine years was similar to that reported in a review of follow-up studies of PD (55). Three possible explanations to the panic-depression co-morbidity have been suggested: depression as a causal risk factor for panic, panic as a causal risk factor for depression or panic and depression both as consequences of another disorder (115).…”
Section: Outcome Of Panic Disorder At Follow-upsupporting
confidence: 81%
“…Roy- Byrne and Cowley [1994] have reviewed follow-up studies in PD and have meticulously described some of the methodological problems involved. These problems also apply to the prediction of nonresponse and all deal with differences between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Information regarding the course of panic disorder is available from retrospective studies, but the results are inconsistent (7)(8)(9). Studies from the 1950s and 1960s found that 40%-60% of patients with panic disorder were either unchanged or slightly improved (10).…”
mentioning
confidence: 99%